Training visual control in wheelchair basketball shooting - Oudejans, R. R. D.; Heubers, S.; Ruitenbeek, J.-R. J. A. C.; Janssen, T. W. J. (Research Quarterly for Exercise and Sport, 2012)
We examined the effects of visual control training on expert wheelchair basketball shooting, a skill more difficult than in regular basketball, as players shoot from a seated position to the same rim height. The training consisted of shooting with a visual constraint that forced participants to use target information as late as possible. Participants drove under a large screen that initially blocked the basket. As soon as they saw the basket they shot. When training with the screen, shooting percentages increased. We conclude that visual control training is an effective method to improve wheelchair basketball shooting. The findings support the idea that perceptualmotor learning can be enhanced by manipulating relevant constraints in the training environment, even for expert athletes.